Discrimination of Women in Film: A Study of Reception Analysis in the Kartini Movie - Hernawan, Aurellia Prisca; Triyono, Agus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Film are present as mass media for delivering messages to audience with purpose of describing social life that occurs in society. Kartini movie is a biographical drama film directed by Hanung Bramantyo that elevates the emancipation fighter Raden Ajeng Kartini in an effort to gain equality and fight againts the culture that limits women. This research is intended to find out how the audience’s reception of gender discrimination experienced by women in the Kartini Movie. The theory used in this research is Stuart Hall’s encoding/decoding model of audience reception. This research uses qualitative approach with an interview data collection method. The results of the interview of the four informants with seven concept of women discrimination in the Kartini Film showed diverse interpretations including dominant-hegemonic posittion, negotiated position, and opposition position. The interpretation of the four informants were motivated by the environment, organization, familiy, and mass media.